Equine Sarcoids - Treatment with a Combination of Acyclovir and Surgical Excision - Rosa, Matheus Camargos de Britto; Campos, Maria Eduarda de Sousa Teixeira; Goulart, Raquel Luísa Lopes; Toma, Hugo Shisei; Pereira, Rodrigo Norberto; Raymundo, Djeison Lutier (Acta Scientiae Veterinariae, 2022)
Background: Sarcoids are the most frequent skin tumors among horses, causing serious lesions due to their different shapes, sizes, degree of invasiveness and distribution on the body. The pathogenesis of sarcoids is multifactorial, with genetic, viral and environmental involvement, making their treatment complex. The aggressiveness and high rate of recurrence of sarcoids makes it difficult to use an effective treatment, which is why there are several therapeutic routes described in the literature. Aiming to describe and expand sarcoid treatments, this paper reports on the use of acyclovir in the treatment of this type of tumor. Cases: Four horses sent to the Large Animal Veterinary Hospital of the Federal University of Lavras - UFLA were diagnosed and treated for sarcoids. Case 1. Lesions on the right ear, region of the masseter muscle of the right side of the face, neck, vulva and medial aspect of the left pelvic limb. Case 2. Lesion in the left groin region. Case 3. Lesions on the face, masseter muscle region on the left side, mandibular region and right ear pinna. Case 4. Lesion in the lateral region of the left pelvic limb, close to the tarsometatarsal joint. All horses had a diagnosis of sarcoid, which was confirmed by histopathological examination of material collected after surgical excision. Macroscopically, the neoplastic lesions were classified as fibroblastic, verrucous and nodular. The tumors exhibited irregular surfaces, keratinization, and a firm consistency. Their surfaces were alopecic, slightly rough, some of them were ulcerated, and their color ranged from greyish to rosy and reddish. All the tumor masses were surgically excised from the 4 horses, and one sarcoid was treated by thermal cauterization with liquid nitrogen due to the lesion’s depth and size. In most cases, the sarcoid removal sites were closed with sutures. Only 2 lesions were not sutured due to the impossibility of bringing the edges of tissue close together, or due to proximity to the tarsometatarsal joint. The surgical wounds were cleaned twice a day with sterile saline solution followed by the topical application of Acyclovir. One of the animals received complementary therapy with Cimetidine. Discussion: The equines recovered completely from their sarcoid treatment, and no recurrences were reported a year later. Thus, the combination of treatments employed for the extirpation of sarcoids proved to have greater chances of success. First, all the tumors were surgically removed with the largest possible margins of safety in order to ensure the elimination of neoplastic cells. In the postoperative period, all the animals received topical treatment of the lesions with acyclovir after surgical resection of the tumors. The drug aided the complete healing of post-surgical wounds, and healing time varied according to the size and depth of the lesion. One tumor was treated with liquid nitrogen after surgical excision of the sarcoid. Another horse was treated with cimetidine over a 3-month period after surgical excision of the neoplasm in order to reduce the sarcoid and prevent its evolution. Surgical excision of the sarcoid associated with topical application of acyclovir ointment showed satisfactory results. Moreover, the combination of surgical excision and administration of liquid nitrogen on the lesion and topical application of acyclovir ointment in the postoperative period also provided good results. Given the complexity of sarcoid treatment and the high recurrence rate of these tumors, the use of combined treatments should be taken into account. Keywords: horses, skin tumor, cutaneous neoplasm, therapy. Título: Sarcoide em equinos - tratamento com associação de Aciclovir e excição cirúrgica Descritores: equinos, tumor de pele, neoplasia cutânea, terapia.